2017
DOI: 10.1038/cddis.2017.66
|View full text |Cite
|
Sign up to set email alerts
|

2-O-Methylmagnolol upregulates the long non-coding RNA, GAS5, and enhances apoptosis in skin cancer cells

Abstract: Magnolol, a hydroxylated biphenol compound isolated from the bark of Magnolia officinalis, has been shown to exhibit anti-proliferative effect in various cancer cells, including skin cancer cells. Methoxylation of magnolol appears to improve its anti-inflammatory activity, yet the effect of this modification on the agent's antitumor activity remains unknown. In this work, we report that 2-O-methylmagnolol (MM1) displays improved antitumor activity against skin cancer cells compared to magnolol both in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 40 publications
(54 reference statements)
4
30
3
Order By: Relevance
“…The increased antitumor activity of MM1 has been shown to correlate with its increased ability to induce apoptosis in skin cancer cells [17]. In the same study, we have presented preliminary data to indicate that such a mechanism also apply to oral cancer cells SAS.…”
Section: Effects Of Magnolol and Mm1 On Apoptosis And Il6-stat3 Pathwsupporting
confidence: 48%
See 3 more Smart Citations
“…The increased antitumor activity of MM1 has been shown to correlate with its increased ability to induce apoptosis in skin cancer cells [17]. In the same study, we have presented preliminary data to indicate that such a mechanism also apply to oral cancer cells SAS.…”
Section: Effects Of Magnolol and Mm1 On Apoptosis And Il6-stat3 Pathwsupporting
confidence: 48%
“…It has been suggested that the improved antitumor activity of MM1 in skin cancer cells may attribute to the upregulation of lncRNA GAS5 and the enhancement of apoptosis [17]. While we have observed that MM1 displays a greater ability than magnolol to induce apoptosis in OSCC cells (Fig.…”
Section: Effects Of Magnolol and Mm1 On Apoptosis And Il6-stat3 Pathwcontrasting
confidence: 38%
See 2 more Smart Citations
“…Zhou et al demonstrated that downregulation of lncRNA MEG3 mediated by DNMT3b contributed to nickel malignant transformation of human bronchial epithelial cells via modulating PHLPP1 transcription and HIF-1α translation (11). Wang et al uncovered that 2-O-Methylmagnolol upregulated the long non-coding RNA, GAS5, and enhanced apoptosis in skin cancer cells (12). Several other studies also demonstrated the function of lncRNAs in BC (13)(14)(15).…”
Section: Introductionmentioning
confidence: 95%